Diastolic stress test echocardiography in patients with suspected heart failure with preserved ejection fraction: a pilot study. (19th November 2018) - Belyavskiy, Evgeny; Morris, Daniel A.; Url‐Michitsch, Marion; Verheyen, Nicolas; Meinitzer, Andreas; Radhakrishnan, Aravind‐Kumar; Kropf, Martin; Frydas, Athanasios; Ovchinnikov, Artem G.; Schmidt, Albrecht; Tadic, Marijana; Genger, Martin; et al.
Abstract: Aims: The purpose of this pilot study was to assess the potential usefulness of diastolic stress test (DST) echocardiography in patients with suspected heart failure with preserved ejection fraction (HFpEF). Methods and results: Patients with suspected HFpEF (left ventricular ejection fraction ≥ 50%, exertional dyspnoea, septal E/e′ at rest 9–14, and N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) at rest < 220 pg/mL; n  = 13) and a control group constituted from asymptomatic patients with arterial hypertension ( n  = 19) and healthy subjects ( n  = 18) were included. All patients were analysed by two‐dimensional and Doppler echocardiography at rest and during exercise (DST) and underwent cardiopulmonary exercise testing and NT‐proBNP analysis during exercise. HFpEF during exercise was defined as exertional dyspnoea and peak VO2  ≤ 20.0 mL/min/kg. In patients with suspected HFpEF at rest, 84.6% of these patients developed HFpEF during exercise, whereas in the group of asymptomatic patients with hypertension and healthy subjects, the rate of developed HFpEF during exercise was 0%. Regarding the diagnostic performance of DST to detect HFpEF during exercise, an E/e′ ratio >15 during exercise was the most accurate parameter to detect HFpEF (accuracy 86%), albeit a low sensitivity (45.5%). Nonetheless, combining E/e′ with tricuspid regurgitation (TR) velocity > 2.8 m/s during exercise provided a significant increase in the sensitivity to detect patients with HFpEF during exercise (sensitivity 72.7%, specificity 79.5%, and accuracy 78%). Consistent with these findings, an increase of E/e′ was significantly linked to worse peak VO2, and the combination of an increase of both E/e′ and TR velocity was associated with elevated NT‐proBNP values during exercise. Conclusions: The findings of this pilot study suggest that DST using E/e′ ratio and TR velocity could be of potential usefulness to diagnose HFpEF during exercise in patients with suspected HFpEF at rest.